When can lotteries improve public procurement processes? - Estache, Antonio,Foucart, Renaud,Serebrisky, Tomás (Inter-American Development Bank, Department of Research and Chief Economist, 2022)
We study the potential benefits of adding a lottery component to cut the main risks associated with standard negotiated and rule-based auction procurement procedures. We show that adopting a two stage approach in which bureaucrats first negotiate with a small number of bidders to assess their eligibility and, next, rely on a lottery to award the contract reduces corruption risks often observed in negotiated procedures. For rule-based procedures, we show that a
10.18235/0004522
Keywords: Graue Literatur; rules; discretion; procurement; lotteries; corruption; auctions